2016
DOI: 10.1111/sji.12437
|View full text |Cite
|
Sign up to set email alerts
|

MICA,MICB Polymorphisms and Linkage Disequilibrium with HLA‐B in a Chinese Mongolian Population

Abstract: In this study, polymorphisms of major histocompatibility complex class I chain-related genes A and B (MICA and MICB) and human leucocyte antigen (HLA)-B gene were investigated for 158 unrelated Chinese Mongolian subjects recruited from central Inner Mongolia Autonomous Region, northern China, by polymerase chain reaction-sequence-based typing (PCR-SBT) and cloning. Collectively, 79 alleles, including 20 MICA, 12 MICB and 47 HLA-B alleles, were identified. MICA*008:01 (21.2%), MICB*005:02 (48.1%) and HLA-B*51:0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 26 publications
0
15
1
Order By: Relevance
“…The second and the third groups composed of 104 Han individuals and 158 Mongols, respectively, were recruited from the Inner Mongolia Autonomous Region, northern China (abbreviated as IMH and IMM in this study, respectively). The MICA*Del distribution has been reported for these two sample panels (Liu et al., ; Wang et al., ) using a typing strategy that required prior information of MICA‐STR (Tian et al., ). The MICA*Del frequencies were used for inter‐population comparison in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second and the third groups composed of 104 Han individuals and 158 Mongols, respectively, were recruited from the Inner Mongolia Autonomous Region, northern China (abbreviated as IMH and IMM in this study, respectively). The MICA*Del distribution has been reported for these two sample panels (Liu et al., ; Wang et al., ) using a typing strategy that required prior information of MICA‐STR (Tian et al., ). The MICA*Del frequencies were used for inter‐population comparison in this study.…”
Section: Methodsmentioning
confidence: 99%
“…An approximately 100‐kb genomic deletion spanning the entire MICA gene ( MICA*Del ) was initially identified on haplotypes bearing HLA‐B*4801 in a Japanese population (Komatsu‐Wakui et al ., ), later on HLA‐B*46 and HLA‐B*15 haplotypes in other ethnic groups (Komatsu‐Wakui et al., ; Aida et al., ). In most cases, MICA*Del is linked to MICB*009N , and to a less extent to MICB*005:02 (Komatsu‐Wakui et al., ; Komatsu‐Wakui et al., ; Aida et al., ; Liu et al., ; Wang et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The HLA genotype was as follows: HLA‐A*02:06 , A*24:02 ; HLA‐B*27:05 , B*44:02 ; MICA*007:07 , MICA*008:01 ; MICB*004:01, MICB*005:02; HLA‐DRB1*03:01 , DRB1*15:01 . Previous studies have demonstrated consistent linkage between MICA*007 and HLA‐B*27:05, and between MICA*008:01 and HLA‐B*44:02 (Fodil et al., ; Wang et al., ), suggesting that MICA*007:07 was linked to HLA‐B*27:05 . MICA*007:07 was associated with MICA*A4 allele in exon 5.…”
Section: Resultsmentioning
confidence: 82%
“…Recently, we reported MICA and MICB allelic distributions in 158 individuals of Mongol ethnicity recruited from the Inner Mongolia Autonomous Region, northern China (Wang et al., ). To investigate further the extent of MICA polymorphism in the Mongolian ethnic group, collecting of new DNA samples has been initiated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation